Blood pyrrole-protein adducts as a diagnostic and prognostic index in pyrrolizidine alkaloid-hepatic sinusoidal obstruction syndrome - Gao H; Ruan JQ; Chen J; Li N; Ke CQ; Ye Y; Lin G; Wang JY (Dove Medical Press, 2015)
Hong Gao,1,* Jianqing Q Ruan,2,* Jie Chen,1 Na Li,2 Changqiang Q Ke,3 Yang Ye,3–5 Ge Lin,2,4,5 Jiyao Y Wang1,61Department of Gastroenterology, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 2School of Biomedical Sciences, Chinese University of Hong Kong, Hong Kong; 3Shanghai Institute of Materia Medica, Shanghai, People’s Republic of China; 4Joint Research Laboratory for Promoting Globalization of Traditional Chinese Medicines, Shanghai Institute of Materia Medica, 5Chinese University of Hong Kong, Hong Kong; 6Center of Evidence-Based Medicine Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this work and share first authorship Background: The diagnosis of hepatic sinusoidal obstruction syndrome (HSOS) induced by pyrrolizidine alkaloids is mainly based on clinical investigation. There is currently no prognostic index. This study evaluated the quantitative measurement of blood pyrrole-protein adducts (PPAs) as a diagnostic and prognostic index for pyrrolizidine alkaloid-induced HSOS.Methods: Suspected drug-induced liver injury patients were prospectively recruited. Blood PPAs were quantitatively measured using ultra-performance liquid chromatography-tandem mass spectrometry. Patients’ age, sex, biochemistry test results, and a detailed drug history were recorded. The patients were divided into two groups, ie, those with HSOS induced by pyrrolizidine alkaloid-containing drugs and those with liver injury induced by drugs without pyrrolizidine alkaloids. The relationship between herb administration, clinical outcomes, blood sampling time, and blood PPA concentration in pyrrolizidine alkaloid-associated HSOS patients was analyzed using multiple linear regression analysis.Results: Forty patients met the entry criteria, among whom 23 had pyrrolizidine alkaloid-associated HSOS and 17 had liver injury caused by drugs without pyrrolizidine alkaloids. Among the 23 patients with pyrrolizidine alkaloid-associated HSOS, ten recovered, four developed chronic disease, eight died, and one underwent liver transplantation within 6 months after onset. Blood PPAs were detectable in 24 of 40 patients with concentrations from 0.05 to 74.4 nM. Sensitivity and specificity of the test for diagnosis of pyrrolizidine alkaloid-associated HSOS were 100% (23/23) and 94.1% (23/24), respectively. The positive predictive value was 95.8% and the negative predictive value was 100%, whereas the positive likelihood ratio was 23.81. The level of blood PPAs in the severe group (died or received liver transplantation) was significantly higher than that in the recovery/chronicity group (P=0.004). Conclusion: Blood PPAs measured by ultra-performance liquid chromatography-tandem mass spectrometry are highly sensitive and specific for pyrrolizidine alkaloid-associated HSOS. The blood PPA concentration is related to the severity and clinical outcome of pyrrolizidine alkaloid-associated HSOS. Keywords: drug-induced liver injury, herb, blood protein adducts, prognostic marker